Neurokinin-1 receptor desensitization attenuates cutaneous active vasodilatation in humans - Wong, Brett J.; Minson, Christopher T. (The Journal of physiology, 2006)
To date, the neurotransmitter(s) and pathways involved in cutaneous active vasodilatation are not fully understood. The purpose of this study was to determine the potential involvement of neurokinin-1 (NK 1 ) receptors to active vasodilatation. Our experimental model exploited our previous findings that repeated microdialysis infusions of substance P desensitize the NK 1 receptors and that substance P-induced vasodilatation contains a substantial nitric oxide (NO) component. Eleven subjects were equipped with four microdialysis fibres on the ventral forearm. Site 1 served as a control and received a continuous infusion of Ringer solution. Site 2 received a continuous infusion of 10 m m l -NAME to inhibit NO synthase. Site 3 received a 10 Î¼ m dose of substance P to desensitize the NK 1 receptors prior to whole-body heating. Site 4 received a 10 Î¼ m dose of substance P combined with 10 m m l -NAME. Red blood cell (RBC) flux was measured via laser-Doppler flowmetry, and cutaneous vascular conductance (CVC) was calculated as RBC flux/mean arterial pressure and normalized to maximal vasodilatation via 28 m m sodium nitroprusside. Substance P was infused for 15 min at 4 Î¼l min â1 in sites 3 and 4, and skin blood flow was allowed to return to baseline (â¼45â60 min). Subjects then underwent a period of whole-body heat stress to raise oral temperature 0.8â1.0Â°C above baseline. Pretreatment with substance P increased CVC to 48 Â± 2% CVC max , which was significantly greater than for sites pretreated with substance P combined with l -NAME (27 Â± 2% CVC max ; P < 0.001). During whole-body heating, CVC in control sites increased to 69 Â± 3% CVC max . Sites pretreated with substance P (48 Â± 3% CVC max ) were significantly reduced compared to control sites ( P < 0.001). The CVC response to whole-body heat stress in l -NAME sites was significantly reduced (32 Â± 3% CVC max ; P < 0.001) compared to both control sites and sites pretreated with substance P. The CVC response to whole-body heating was nearly abolished in sites pretreated with substance P combined with l -NAME (20 Â± 2% CVC max ) and was significantly reduced compared to the other three sites (all P < 0.001). These data suggest NK 1 receptors contribute to active vasodilatation and that combined NK 1 receptor desensitization and NO synthase inhibition further diminishes active vasodilatation.